Does country governance and bank productivity Nexus matters?. Issue 2 (7th October 2020) - Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina; Md. Nassir, Annuar; Sufian, Fadzlan; Tan, Khar Mang; Iqbal Hussain, Hafezali
Abstract : Purpose: This study aims to examine the impact of country governance and other potential bank-specific characteristics and macroeconomic condition determinants on bank productivity in the period of 2006–2016. Design/methodology/approach: The productivity level of total 167 banks selected from Malaysia, Indonesia, Brunei and Singapore are evaluated using the data envelopment analysis-based Malmquist productivity index method. A panel regression analysis framework based on ordinary least squares, a fixed effect and a random effect models then are used to identify its main determinants. Findings: The empirical findings indicate that the total factor productivity changes of Islamic banks is higher than conventional banks. The liquidity and global financial crisis influence both banks' productivity. Bank size, credit risk, market power, management efficiency and inflation merely influence Islamic banks' productivity. On the country governance dimensions, voice and accountability are found to positively influence both banks' productivity. Regulatory quality and rule of law (RL) significantly influences the conventional parts. Political stability and absence of violence, government effectiveness, RL and control of corruption negatively influence the banks' productivity, but this influence is only significant for the Islamic banks. Originality/value: Country governance has received surprisingly little attention in the banking industry over the past few decades. Majority of the studies that examine the effect of governance on bank performance have focused more on the micro governance dimension. Thus, to the best of the researcher's knowledge, no study has been done to address the effect of country governance on the productivity of the Islamic and conventional banks.